Influence of Preseason Versus In-Season Play on Achilles Tendon Injuries in the National Football League. Issue 12 (6th December 2021) - Ready, Lauren V.; Li, Neill Y.; Worobey, Samantha; Lemme, Nicholas J.; Yang, Daniel S.; Yang, JaeWon; Krill, Michael; Owens, Brett D.
Background: A ruptured Achilles tendon (AT) can sideline a player for 6 to 12 months and reduce their power rankings by more than 50%. Previous research has compared AT rupture rates in different game conditions. Purpose: To determine environmental and physiological risk factors for AT tears, given the minimal amount of research on AT ruptures in the National Football League (NFL). Study Design: Case series; Level of evidence, 4. Methods: NFL players with a diagnosed AT tear between 2009 and 2016 were selected as the study population for this retrospective analysis. Data on NFL injury were collected from an established database composed of publicly available information. Player profiles were employed to determine position, team, and game statistics at the time of injury. The proportion of NFL rookies was approximated by summing the number of draft picks and the number of signed, undrafted free agents and measured against the number of roster spots before the season. Results: Between 2009 and 2016, there were 101 documented AT tears. Of these, 64% (65/101) occurred before the official season, including preseason games. Of the 36 tears that occurred in-season, 34 were during games. Overall, 29% (19/65) of the preseason tears occurred in rookies and 100% (36/36) of the in-season tears affected nonrookies. Of the rookies with AT ruptures, 42.11% returned to play in the NFL, while 62.20% of the nonrookies came back to partake in future seasons. Despite an average age of 26.7 years, the tear distribution was bimodal with players aged 24 and 36 years exhibiting the highest rates of tear. Conclusion: In our review of AT tears in NFL athletes, a large percentage of the tears occurred in rookie players, especially during the preseason. We also found that tears during the season occurred in only nonrookies, suggesting that the preseason is when rookies experience the greatest risk for injury.